2018
DOI: 10.1111/ijlh.12929
|View full text |Cite
|
Sign up to set email alerts
|

The CD9+CD11bHLADR immunophenotype can be used to diagnose acute promyelocytic leukemia

Abstract: Objective To investigate the immunophenotypic characteristics of acute promyelocytic leukemia (APL) and explore the sensitivity and specificity of various antibody combinations for the timely and accurate diagnosis APL. Methods A retrospective analysis was performed using morphological, immunological, genetic, and molecular biological data from 92 patients diagnosed with APL and 190 controls diagnosed with non‐APL acute myeloid leukemia. Results For APL diagnosis, the CD9/CD11b/human leukocyte antigen (HLA)‐DR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 21 publications
1
16
0
Order By: Relevance
“…By the BMA statistics, we also noted that CD56 contributes signi cantly to APL screening ( Figure 2), which was just mentioned as a low expression marker in the disease compared to other types of AML [11,13,14,[16][17][18][19][20]. Clinically, patients without CD56 expression have a better prognosis compared to others when treated with the ATRA agent [27][28][29][30][31][32].…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…By the BMA statistics, we also noted that CD56 contributes signi cantly to APL screening ( Figure 2), which was just mentioned as a low expression marker in the disease compared to other types of AML [11,13,14,[16][17][18][19][20]. Clinically, patients without CD56 expression have a better prognosis compared to others when treated with the ATRA agent [27][28][29][30][31][32].…”
Section: Discussionmentioning
confidence: 98%
“…Thus, the absence of these antigens in AML cells leading to a similar pattern to APL cells that makes di culties in APL diagnosis. Previous studies have shown the high diagnostic values of cell antigens for APL but with a comparison to an AML control group containing a high percentage of HLA-DR-positive subjects [11][12][13][14][15][16]. Only two studies assessed the diagnostic role of cell antigens for APL in comparison to an HLA-DR-negative AML control group and showed high sensitivity, speci city, and accuracy values (98-100%) [20,21].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some immunophenotypic markers as CD34, CD117, HLA-DR, CD13, CD9, CD18, CD2, and CD11a, CD11b might be helpful to guide the APL diagnosis in a fasting method with turnaround time just in two hours [10]. Previous studies have shown that combination some these antigens help to detect APL with high accuracy, sensitivity, and specificity [11][12][13][14][15][16]. In reality, the morphology and immuno-phenotype of APL are different from HLA-DRpositive AML.…”
Section: Introductionmentioning
confidence: 99%